LEADERSHIP, COMMITMENT AND WORK CULTURE : THEIR IMPACT ON EMPLOYEE PRODUCTIVITY - Ibrahim Ahmad; Haeruddin Haeruddin; Muhammad Abbas; Syarifuddin Arief (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
Purpose of this study was to determine and analyze the influence of leadership, commitment, budaya commitmentto employee productivity at the Department of Rural Community Empowerment of North Morowali Regency. Penelitian ini mengguna-This study uses a quantitative descriptive approach with a population of 33 people by sampling using the saturated sample Method. The analysis method used is linear regression analysis method. The results obtained are leadership has no significant effect on employee productivity, commitment psoitif psoitif significant effect on employee productivity, BUpower of work has no significant effect on employee productivity. Commitment is the dominant variable affecting employee performance and simultaneously the three variables studied have a positive and significant effect on employee productivity.